Tissue Pharmacology of Da-Cheng-Qi Decoction in Experimental Acute Pancreatitis in Rats. (23rd June 2015) - Zhao, Xianlin; Zhang, Yumei; Li, Juan; Wan, Meihua; Zhu, Shifeng; Guo, Hui; Xiang, Jin; Thrower, Edwin C.; Tang, Wenfu
Abstract : Objectives . The Chinese herbal medicine Da-Cheng-Qi Decoction (DCQD) can ameliorate the severity of acute pancreatitis (AP). However, the potential pharmacological mechanism remains unclear. This study explored the potential effective components and the pharmacokinetic characteristics of DCQD in target tissue in experimental acute pancreatitis in rats. Methods . Acute pancreatitis-like symptoms were first induced in rats and then they were given different doses of DCQD (6 g/kg, 12 g/kg, and 24 g/kg body weight) orally. Tissue drug concentration, tissue pathological score, and inflammatory mediators in pancreas, intestine, and lung tissues of rats were examined after 24 hours, respectively. Results . Major components of DCQD could be found in target tissues and their concentrations increased in conjunction with the intake dose of DCQD. The high-dose compounds showed maximal effect on altering levels of anti-inflammatory (interleukin-4 and interleukin-10) and proinflammatory markers (tumor necrosis factor α and interleukin-6) and ameliorating the pathological damage in target tissuesP < 0.05 . Conclusions . DCQD could alleviate pancreatic, intestinal, and lung injury by altering levels of inflammatory cytokines in AP rats with tissue distribution of its components.